Effects of dietary probiotic microcapsules Bacillus cereus P22 and Staphylococcus lentus L1k on growth performance, immune response, and resistance of African catfish, Clarias gariepinus Burchell 1822 infected with Aeromonas hydrophila - Lilik Setiyaningsih; Widanarni Widanarni; Angela Mariana Lusiastuti; Munti Yuhana (Jurnal Iktiologi Indonesia, 2017)
The aimed of this research was to evaluate the effects of dietary probiotic microcapsules B.cereus P22 and S. lentus (L1k) at different dose and frequency on growth performance, immune response and resistance of African catfish infected with A. Hydrophila. Probiotics used in this study were B. cereus P22 and S. lentus L1k encapsulated by spray draying method. The research was carried out for 56 days with eight treatments and four replications. The treatments were K- (negative control), K+ (positive control), A (feed supplemented with 0,5% of microencapsulated probiotic, fedevery day), B (feed supplemented with 0,5% of microencapsulated probiotic, fed once every three days), C (feed supplemented with 1% of microencapsulated probiotic, fed every day), D (feed supplemented with 1% of microencap-sulated probiotic with an administration once every three days), E (feed with 2% of microencapsulated probiotic with an administration every day) and F (feed with 2% of microencapsulated probiotic with an administration once every three days). On day 42, all of the fish except K- were challenged by intramuscular injection of A. hydrophila (108 CFU ml-1). In 40 days after infection, there were no significant difference on survival rate (SR) between treatments (p> 0.05). Treatment E displayed the higher growth rate (4,54±0,02%), total probiotic B. cereus (P22) and S . lentus (L1k) (4.06± 0.09 log CFU g-1; 4.02±0.08 log CFU g-1) than other treatments; whereas treatment D showed the best feed conversion rasio(1.191±0.013), and treatment F offered the highest total bacterial count (7.11±0.53 log CFU g-1). An administration of 2% microencapsulated probiotic in every day frequency demonstrated the better growth performance, immune res-ponse and resistance of African catfish to A. hydrophila compare with other treatments. Abstrak Penelitian ini bertujuan untuk mengkaji dosis dan frekuensi pemberian mikrokapsul probiotik melalui pakan terhadap kinerja pertumbuhan, respons imun, dan resistensi ikan lele yang diinfeksi Aeromonas hydrophila. Penelitian ini meng-gunakan Bacillus cereus P22 dan Staphylococcus lentus L1k yang telah dienkapsulasi melalui metode spray draying. Penelitian ini dilaksankan selama 56 hari dengan delapan perlakuan dan empat ulangan, terdiri atas perlakuan K- (kon-trol negatif), K+ (kontrol positif), A (pakan+mikrokapsul probiotik dosis 0,5% frekuensi setiap hari), B (pakan+mikro-kapsul probiotik dosis 0,5% frekuensi tiga hari sekali), C (pakan+mikrokapsul probiotik dosis 1% frekuensi setiap hari), D (pakan+mikrokapsul probiotik dosis 1% frekuensi tiga hari sekali), E (pakan+mikrokapsul probiotik dosis 2% fre-kuensi setiap hari) dan F (pakan+mikrokapsul probiotik dosis 2% frekuensi tiga hari sekali). Ikan diuji tantang dengan A. hydrophila pada hari ke 42 dengan kepadatan 108 CFU ml-1 secara intramuscular (kecuali K- diinjeksi dengan phos-phate buffer saline). Setelah 40 hari pascainjeksi, laju sintasan tidak menunjukkan perbedaan yang signifikan antarperlakuan (p>0,05).Perlakuan E menunjukkan laju pertumbuhan (4,54±0,02%) dan total probiotik B. cereus (P22) dan S. lentus (L1k) (4,06±0,09 log CFU g-1; 4,02±0,08 log CFU g-1) tertinggi; sementara perlakuan D memberikan hasil nisbah konversi pakan terbaik (1,191±0,013), perlakuan F menunjukkan total bacterial count tertinggi (7,11±0,53 log CFU g-1). Hasil penelitian menunjukkan bahwa dosis 2% yang diberikan setiap hari memberikan hasil yang lebih baik dalam meningkatkan laju pertumbuhan, respons imun, dan resistensi ikan lele terhadap A. hydrophila.